Urban-rural variation in mortality and hospital admission rates for unintentional injury in Ireland. Issue 1 (3rd February 2005) - Boland, M; Staines, A; Fitzpatrick, P; Scallan, E
Abstract : Objective: To explore urban-rural differences in the mortality and hospital admission rates for unintentional injuries in the Republic of Ireland. Design: Standardised mortality ratios (SMRs) in residents of urban and non-city areas (called rural areas) from all causes of unintentional injury were calculated using Central Statistics Office mortality data from 1980–2000. Hospital admission data (Hospital In-Patient Enquiry) from 1993–2000 were used to calculate standardised hospital admission ratios (SARs) in urban and rural residents. Population data were obtained from the 1981, 1986, 1991, and 1996 censuses. Results: The rate of unintentional injury mortality was significantly higher in rural residents for all-cause unintentional injury mortality (SMR 103.0, 95% confidence interval 101 to 105), and specifically for deaths related to motor vehicle trauma (MVT), drowning, machinery, and firearms. There were significantly higher SMRs in urban residents for falls and poisoning. The rate of unintentional injury hospital admission was significantly higher in rural residents for all-cause unintentional injury (SAR 104.6, 95% confidence interval 104 to 105) and specifically for injuries from falls, MVT, being struck by or against an object, injuries in pedal cyclists, fire/burn injuries, and machinery injuries. SARs were significantly higher in residents of urban areas for poisoning and injuries in pedestrians. Conclusions: There are urban-rural differences in mortality and admissions for injuries in Ireland. Possible reasons for the higher rural mortality rates are higher case fatality in MVT and rural exposure to hazardous farm machinery, firearms, and open areas of water. This information could assist in targeting prevention programmes under the proposed National Injury Prevention Strategy.